Hegemonic Masculinity and its Manifestations in Wajdi Al-Ahdal's Novel A Land without Jasmine - Nada Ezzadeen Al-Osime (الآداب للدراسات اللغوية والأدبية)
The research aims to discuss the concept of hegemonic masculinity and its influence on societies. It tries to explain the origin of hegemonic masculinity's concept, and how the thinkers, and philosophers discussed this term, and what they wrote about it. It discusses many concepts such as masculinity, patriarchal system and tribal society, and as well as the status of women in the Yemeni society. It also explores aspects of hegemonic masculinity through the events of Wajdi Al-Ahdal's novel A Land without Jasmine. This research is divided into introduction and three sections; the first discusses the concept of hegemonic masculinity, the second explains the hegemonic masculinity and Patriarchal culture in the Yemeni society, the third clarifies manifestations of hegemonic masculinity, such as early marriage and depriving women of education and the conclusion. This research reached many results such as Yemeni society is considered a male-dominated society and the system that prevails in it is the patriarchal system. Furthermore, upbringing and social traditions have contributed to reinforcing a culture of male dominance in society.